PENGARUH MOTIVASI DAN PELATIHAN TERHADAP KINERJA KARYAWAN PT BANK CENTRAL ASIA, TBK KCU MATRAMAN JAKARTA - Agus MD Simamora; Arry Dwi Syahputra (Jurnal Manajemen Bisnis Krisnadwipayana, 2023)
The purpose to determine the effect of motivation and training on employee performance PT. Bank Central Asia, Tbk KCU Matraman Jakarta. This research is included in the category of causal associative research using a quantitative approach. The research population amounted to 68 people, the sampling technique used a saturated sample, all members of the population were used as samples totaling 68 employees of PT. Bank Central Asia, Tbk KCU Matraman Jakarta. The research method uses partially and simultaneous linear regression analysis. The results of the study indicate that in partially or simultaneous ways, motivation and training have a positive and significant effect on the performance of employees of PT. Bank Central Asia, Tbk KCU Matraman Jakarta